Population Structure and Genomic Characterisation of the Ashanti Dwarf Pig of Ghana - Aryee, S.N.D.; Owusu-Adjei, D.; Osei-Amponsah, R.; et al. (Animals, 2024)
There is still limited information on the genomic structure and genetic diversity of African pigs. Genetic diversity studies can contribute significantly to the genetic improvement and conser vation of African pigs. This study presents a genetic diversity analysis and population structure of pig breeds in Ghana, with a focus on the Ashanti Dwarf pig (ADP), an indigenous pig breed of Ghana. A total of 167 pigs sampled in Ghana and populations consisting of Ashanti Dwarf pigs (n = 106), exotics (mostly European pigs) (n = 11), crosses (between indigenous and exotic breeds) (n = 44), and unknown breeds (nondescript) (n = 6) were genotyped using Porcine SNP60K BeadChip. Moderate heterozygosity levels, ranging from 0.28 for Ashanti Dwarf pigs to 0.31 for exotic pigs (mostly European pigs), were observed. Principal component analysis of the pig populations within Ghana resulted in two distinct clusters of pigs: (i) Northern and (ii) Southern regional clusters. The PCA based on breed also resulted in four clusters: (i) ADPs; (ii) exotics (iii) crossbreeds between ADP and exotics; (iv) unknown breed types. The PCA demonstrated that the clustering was influenced by genetics, geographical location, production systems, and practices. ADMIXTURE-based analysis also showed that the populations within Ghana are admixed. FST analysis revealed SNPs associated with QTLs for traits such as disease resilience and growth among ADP populations within the different regional and ecological zones of Ghana.
Research Article
Keywords: animal genetic resource; African pigs; genetic diversity